Chlorophyll 2017
DOI: 10.5772/67913
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Emitting Diodes: Progress in Plant Micropropagation

Abstract: In commercial micropropagation laboratories, the light source is one of the most important factors controlling plant morphogenesis and metabolism of plant cells and tissue and organ cultures. Lamp manufacturers have begun to rate lamps specifically for plant needs. The traditional light source used for in vitro propagation is fluorescent lamps (FLs). However, power consumption in FL use is expensive and produces a wide range of wavelengths (350-750 nm) unnecessary for plant development. Light-emitting diodes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 28 publications
(28 reference statements)
0
22
1
2
Order By: Relevance
“…It was previously reported that blue LED light alone increased chlorophyll content in F. benjamina, Anthurium andraeanum Linden ex André, and Phalaenopsis sp. (Werbrouck et al 2012;Bello-Bello et al 2017). However, in the present study, the NS1 lamp, with an increased blue light content, did not improve the results.…”
Section: Resultscontrasting
confidence: 86%
See 1 more Smart Citation
“…It was previously reported that blue LED light alone increased chlorophyll content in F. benjamina, Anthurium andraeanum Linden ex André, and Phalaenopsis sp. (Werbrouck et al 2012;Bello-Bello et al 2017). However, in the present study, the NS1 lamp, with an increased blue light content, did not improve the results.…”
Section: Resultscontrasting
confidence: 86%
“…To date, several light sources have been utilized in plant tissue culture laboratories including high-pressure sodium, metal halide, and fluorescent lamps, with the latter light sources being most popular (Gupta and Jatothu 2013). Fluorescent lamps (FLs) are versatile, as they provide a wide light spectrum (350-750 nm), which is applicable to numerous plant species, although their disadvantages include high electricity consumption, unstable radiation parameters, and considerable heat emission (Bello-Bello et al 2017). Light-emitting diodes (LEDs), on the other hand, have the flexibility to deliver specific wavelengths that may yield faster or more favorable results for plant researchers and growers.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our results, the beneficial effects of some LED light sources on the induction of embryogenesis in Oncidium have been reported [ 39 ]. Due to these beneficial effects, LED light systems are being increasingly used to boost the horticulture industry in Taiwan and several other countries [ 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chlorophyll a content was significantly higher in the blue LED treatment (0.2813 mg g −1 fresh weight), while chlorophyll b content was higher in blue and the combination of blue and red LED treatments, yielding 0.1368 and 0.1468 mg g −1 fresh weights, respectively. Total chlorophyll (0.421875 mg g −1 fresh weight) was highest under blue LED while the lowest total chlorophyll content was found in FL treatments and white LEDs yielding 0.1810 and 0.2500 mg g −1 fresh weights, respectively 29 . We have summarized the effects of electric lights on the growth and development of other ornamentals studied in recent years in Supplementary Table S1 .…”
Section: A Recent Account Of Indoor Light Qualities On Plant Growth Amentioning
confidence: 90%
“…Ornamental plants serve as good case studies for the testing of narrow-bandwidth electric lights such as LEDs, because they are in general smaller in size, consume fewer resources, have easily amenable features of broad esthetic values and are already accustomed to growth under indoor (home- or office-spaces) conditions compared to crop plants. In the case of Anthurium ( Anthurium andreanum ) and moth orchids ( Phalaenopsisis ), they not only displayed positive development but also yielded higher biochemical content when grown under LED lights (white light at 460 and 560 nm peaks; red at 660 nm peak and blue at 460 nm peak) compared to those grown under fluorescent lights (545–610 nm) (FL) 29 . In this study, the PPFD was maintained at 25 μmol m −2 s −1 under a 16 h photoperiod.…”
Section: A Recent Account Of Indoor Light Qualities On Plant Growth Amentioning
confidence: 99%